1980
DOI: 10.5014/ajot.34.7.452
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Vestibular-based Functions in Pre-School Children

Abstract: A 21-item test entitled Assessment of Sensorimotor Integration in Pre-School Children (1) was developed to measure vestibular-based functions in pre-school children. It focuses on postural control, reflex integration, and bilateral motor integration. Data were gathered on 113 normal and 23 developmentally delayed children from three to five years of age. The psychometric quality of the test was investigated in terms of domain validity, discriminant validity, and interobserver reliability. It was found that 1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Much research supports a correlation between motor dysfunction and attention deficits (Brossard-Racine et al, 2011; Kadesjo and Gillberg, 1998; Kaplan et al, 1998) with about half of children with ADHD meeting criteria for DCD and vice versa (Kadesjo and Gillberg, 1998). Research in older children has shown ATNR retention to be predictive of academic achievement (Jordan-Black, 2005; McPhillips and Jordan-Black, 2006), motor score (DeGangi et al, 1980) and ADHD (Konicarova and Bob, 2013). Whilst the ATNR was one of three primitive reflexes measured by two review studies (Gieysztor et al, 2018; Pecuch et al, 2021), both papers limited reflex comparison to total motor scores, with Gieysztor et al (2018) further limiting comparisons to total reflex score, preventing extrapolation of specific reflex retention relationships to specific motor functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much research supports a correlation between motor dysfunction and attention deficits (Brossard-Racine et al, 2011; Kadesjo and Gillberg, 1998; Kaplan et al, 1998) with about half of children with ADHD meeting criteria for DCD and vice versa (Kadesjo and Gillberg, 1998). Research in older children has shown ATNR retention to be predictive of academic achievement (Jordan-Black, 2005; McPhillips and Jordan-Black, 2006), motor score (DeGangi et al, 1980) and ADHD (Konicarova and Bob, 2013). Whilst the ATNR was one of three primitive reflexes measured by two review studies (Gieysztor et al, 2018; Pecuch et al, 2021), both papers limited reflex comparison to total motor scores, with Gieysztor et al (2018) further limiting comparisons to total reflex score, preventing extrapolation of specific reflex retention relationships to specific motor functions.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, primitive reflex assessment is readily utilized to identify neurological pathology in the infant (Jordan-Black, 2005). However, employment of modified position testing in older age groups has shown persisting reflexes to be associated with reading difficulties and dyslexia (McPhillips and Jordan-Black, 2006), speech-language disorders (Adamovic et al, 2014), ADHD (Konicarova and Bob, 2013), and motor deficiency (DeGangi et al, 1980; Freides et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rehabilitation literature often refers to observations of conjugate eye movements as measures of the integrity of the vestibular system (e.g., DeGangi, Berk, & Larsen, 1980;Weeks, 1979). Conjugate eye movements are those in which both eyes move in parallel fashion.…”
Section: Oculomotor Functionmentioning
confidence: 99%
“…Rapin (1974) reviewed the clinical records of 353 children under 10 years of age who had been tested with caloric stimulation and the torsion swing under blindfolded conditions. DeGangi et al (1980) studied 23 3-5-year-old children with delays in the acquisition of gross and fine motor skills and, to a lesser extent, language. Ten of these 22 children did not walk until 18 months of age or later, with some not walking until 48 months of age.…”
Section: A Syndromes With Motor Delay or Dysfunctionmentioning
confidence: 99%